Soft PVC (polyvinyl chloride) composition as well as preparation method and application thereof

By adding heat stabilizers, lubricants and other additives to the soft PVC composition, the shortcomings of traditional soft PVC materials in terms of scratch resistance and chemical reagent resistance are solved, and higher surface smoothness and chemical stability are achieved.

CN119529448AInactive Publication Date: 2025-02-28NINGBO HANJI POLYMER MATERIAL CO LTD +1
View PDF 17 Cites 0 Cited by

Patent Information

Application Number
CN202510080797.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional soft PVC materials have shortcomings in improving the smoothness of injection molded edge surfaces and chemical reagent resistance, and it is difficult to meet the needs of higher performance.

Method used

The scratch resistance and chemical reagent resistance of the material are improved by adding heat stabilizers (such as calcium-zinc stabilizers and barium-zinc stabilizers), lubricants (such as oxidized polyethylene wax and calcium stearate), acrylate processing aids and phosphites to the soft PVC composition.

Benefits of technology

This technical method significantly improves the scratch resistance and chemical reagent resistance of soft PVC, so that it maintains stable performance under various chemical environments, and enhances the hardness and wear resistance of the surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of modified plastics, in particular to a soft PVC composition as well as a preparation method and application thereof. The soft PVC composition is prepared from the following components in parts by weight: 50 parts of PVC resin, 15 to 40 parts of a plasticizer, 2.5 to 4.5 parts of a heat stabilizer, 1 to 2 parts of an acrylate processing aid, 0.3 to 0.9 part of a lubricant and 0.1 to 0.3 part of phosphite ester, the heat stabilizer comprises at least one of a calcium-zinc stabilizer and a barium-zinc stabilizer; the lubricant comprises at least one of oxidized polyethylene wax and calcium stearate. The heat stabilizer is adopted, so that the chemical reagent resistance of PVC can be improved, and the PVC can keep stable performance in various chemical environments; by adopting the lubricant, the scratch resistance of the PVC can be improved to a certain extent, and in addition, the hardness and the wear resistance of the PVC surface can be enhanced by adding the acrylate processing aid, so that the scratch resistance of the PVC surface is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of modified plastics, and in particular to a soft PVC composition and a preparation method and application thereof. Background Art

[0002] PVC (polyvinyl chloride) is a popular and widely used synthetic material in the world today. Its global usage ranks second among various synthetic materials. PVC is produced and used worldwide at a growth rate of 4% per year. Soft PVC can also be used in automobile triangular window injection molding due to its advantages of easy molding, easy coloring, low cost and strong plasticity.

[0003] In order to maintain the smooth surface of the injection molding edge, matte or frosted texture treatment is usually used to improve the scratch resistance and chemical resistance of the material surface. However, if you want to further improve the surface smoothness of the injection molding edge, traditional PVC materials are difficult to meet the requirements and need to be modified to obtain higher performance materials. Summary of the invention

[0004] In order to solve the problem that the scratch resistance and chemical resistance of soft PVC need to be further improved, the present application provides a soft PVC composition, which improves the scratch resistance and chemical resistance of the material by using a heat stabilizer and a lubricant.

[0005] In the first aspect, the present application provides a soft PVC composition, which adopts the following technical solution: A soft PVC composition comprises the following components in parts by weight: 50 parts of PVC resin, 15-40 parts of plasticizer, 2.5-4.5 parts of heat stabilizer, 1-2 parts of acrylic ester processing aid, 0.3-0.9 parts of lubricant, and 0.1-0.3 parts of phosphite; The heat stabilizer includes at least one of a calcium zinc stabilizer and a barium zinc stabilizer; The lubricant includes at least one of oxidized polyethylene wax and calcium stearate.

[0006] By adopting the above technical scheme, the lubricant plays a role in reducing the friction between molecular chains during the processing of PVC, which helps to improve the fluidity and processing performance of PVC. At the same time, the lubricant can also form a lubricating film on the surface of PVC products to reduce friction and scratches with the outside world. The lubricant in this formula includes at least one of oxidized polyethylene wax and calcium stearate. These lubricants not only have a good lubricating effect, but also can improve the scratch resistance of PVC to a certain extent. Acrylic acid ester processing aid compounds have excellent adhesion and wear resistance, and can be used to improve the surface properties of PVC. In this formula, the addition of acrylic acid ester processing aids can enhance the hardness and wear resistance of the PVC surface, thereby improving its scratch resistance.

[0007] Heat stabilizers are essential additives in the processing of PVC, used to prevent adverse effects caused by thermal decomposition of PVC during processing and use. The heat stabilizer in this formula includes at least one of calcium zinc stabilizer and barium zinc stabilizer. These stabilizers can react with unstable groups in PVC to form stable compounds, thereby inhibiting thermal decomposition and light aging of PVC. At the same time, they can also improve the chemical resistance of PVC, so that it can maintain stable performance in various chemical environments.

[0008] Phosphite compounds have excellent antioxidant and anti-aging properties and can be used to improve the chemical resistance of PVC. In this formula, the addition of phosphite can further enhance the antioxidant capacity of PVC and prevent its performance from deteriorating when it is corroded by chemical reagents.

[0009] Preferably, the heat stabilizer is a mixture of a calcium zinc stabilizer and a barium zinc stabilizer.

[0010] By adopting the above technical scheme, the calcium zinc stabilizer has good processing performance and can meet the requirements of various processing technologies, such as extrusion, injection molding, blow molding, etc. Its good lubricity and coupling effect can enhance the wrapping with the resin and improve the performance of the product. The barium zinc stabilizer can significantly improve the hardness and strength of PVC, making the product more durable. The barium zinc stabilizer has excellent thermal stability and light stability, which can effectively extend the service life of PVC products. The barium zinc stabilizer has little effect on the transparency of PVC products and can maintain the good light transmittance of the product.

[0011] Calcium zinc stabilizers and barium zinc stabilizers have certain complementarity in performance. Calcium zinc stabilizers excel in processing performance and environmental protection, while barium zinc stabilizers excel in improving hardness and strength. Mixing the two can give full play to their respective advantages, so that PVC products show superior performance in many aspects. Calcium zinc and barium zinc stabilizers may produce a synergistic effect in the mixture, further enhancing the thermal stability and chemical resistance of PVC. This synergistic effect may come from the interaction between them, making the mixture more effective in inhibiting PVC degradation.

[0012] Preferably, the mass ratio between the calcium zinc stabilizer and the barium zinc stabilizer is 1:1-2.5.

[0013] By adopting the above technical scheme, the barium zinc stabilizer can significantly improve the hardness and strength of PVC, which is where the calcium zinc stabilizer is relatively weak. If the content of the barium zinc stabilizer is too low, it may not meet the hardness and strength requirements of PVC products, thereby reducing the scratch resistance. The barium zinc stabilizer has excellent thermal stability and can effectively protect PVC from decomposition at high temperatures. Too low a content may lead to insufficient thermal stability and affect the service life of PVC products. The calcium zinc stabilizer and the barium zinc stabilizer may produce a synergistic effect in the mixture, further enhancing the performance of PVC. If the content of the barium zinc stabilizer is too low, this synergistic effect may be weakened, thereby affecting the overall performance of the PVC product.

[0014] Although barium zinc stabilizers can improve the hardness and strength of PVC, excessive content may have an adverse effect on processing performance, such as increasing resistance during extrusion or injection molding. Barium zinc stabilizers may have a certain impact on the transparency of PVC products. Excessive content may cause the product color to be dark or the light transmittance to decrease, affecting the appearance quality of the product.

[0015] Preferably, the average polymerization degree of the PVC resin is 600-800.

[0016] By adopting the above technical solution, too low a degree of polymerization may limit the processing performance of the resin, such as excessive fluidity during injection molding, making it difficult to control the molding size. PVC resins with a low degree of polymerization have shorter molecular chains and relatively weak intermolecular forces, which may lead to a decrease in physical properties such as tensile strength and impact strength of the products. PVC resins with an average low degree of polymerization may be more susceptible to thermal degradation during processing, resulting in unstable product quality and being more susceptible to corrosion by chemical reagents.

[0017] Although PVC resins with a higher degree of polymerization may have better physical properties (such as hardness) in some aspects, too high a degree of polymerization may lead to reduced toughness and increased brittleness of the product, affecting the chemical resistance of the product.

[0018] Preferably, the soft PVC composition further comprises a nucleating agent, and the nucleating agent comprises at least one of tert-butyl aluminum benzoate, aluminum benzoate, potassium benzoate and lithium benzoate.

[0019] Preferably, the nucleating agent is at least one of aluminum tert-butyl benzoate and aluminum benzoate.

[0020] By adopting the above technical solution, the nucleating agent plays a role of heterogeneous nucleation in PVC, which can refine the grains of PVC. After the grains are refined, the surface of the PVC product is more uniform and delicate, reducing the possibility of stress concentration and scratches caused by coarse grains. The addition of nucleating agents can also improve the toughness of PVC, making it more resistant to deformation when facing external forces. This improvement in toughness helps to reduce the generation and expansion of scratches.

[0021] PVC is a polar polymer material, and nucleating agents such as aluminum tert-butyl benzoate and aluminum benzoate also have certain polarity. According to the principle of similar polarity, polar components have good compatibility with each other. Therefore, these nucleating agents have good compatibility with PVC and can be evenly dispersed in PVC to exert better nucleating effect.

[0022] Preferably, the weight portion of the nucleating agent is 0.1-0.3 parts.

[0023] By adopting the above technical solution, if the amount of nucleating agent is too low, its effect of promoting crystallization will not be obvious. This may lead to insufficient crystallinity of the polymer material, thereby affecting its physical properties and processing properties. Excessive nucleating agent is difficult to further improve the performance and scratch resistance.

[0024] In a second aspect, the present application provides a method for preparing a soft PVC composition, using the following technical solution: A method for preparing a soft PVC composition, used for preparing the above-mentioned soft PVC composition, comprises the following steps: High-speed mixing: mixing the formulated amount of PVC resin, plasticizer, heat stabilizer, acrylic processing aid, lubricant and phosphite with high-speed stirring to obtain a preliminary mixture, wherein the stirring speed of the high-speed stirring is 500-600 rpm; Cooling and mixing: the initial mixture is further subjected to low-speed stirring and cooling and mixing to obtain a final mixture, wherein the stirring speed of the low-speed stirring is 20-40 rpm; Extrusion granulation: The final mixture is subjected to extrusion granulation to obtain a soft PVC composition.

[0025] By adopting the above technical solution, the raw materials such as PVC resin, plasticizer, heat stabilizer, acrylic processing aid, lubricant and phosphite in the formula can be quickly and fully mixed together through high-speed stirring at 500-600rpm. The shear force and friction force generated by high-speed stirring are conducive to the interaction and dispersion between the raw materials, thereby improving the uniformity of mixing.

[0026] After the initial mixture is mixed at high speed, a slow stirring and cooling mixing at 20-30rpm will help to further consolidate the mixing effect. Slow stirring can reduce heat accumulation during the mixing process and ensure that the components remain evenly distributed during the cooling process.

[0027] Preferably, in the high-speed mixing step, the termination temperature of the high-speed mixing is 100-125°C; and in the cooling mixing step, the cooling temperature of the cooling mixing is ≤55°C.

[0028] By adopting the above technical solution, during the high-speed mixing stage, as the high-speed rotation causes friction between the materials to generate heat, the temperature continues to increase. When the temperature is raised to the range of 100-125°C, it is helpful to melt and disperse additives such as plasticizers, heat stabilizers, and acrylic processing aids. These additives are easier to mix evenly with the PVC resin in a molten state to form a stable initial mixture. Appropriate heating temperature can reduce the viscosity of the raw materials, making them easier to be sheared and dispersed during high-speed stirring. This helps to improve mixing efficiency and shorten mixing time. At too high a temperature, the PVC resin is prone to thermal decomposition, producing harmful gases and reducing material performance.

[0029] During the cooling and mixing stage, cooling the initial mixture to ≤55℃ helps consolidate the mixing effect. During the cooling process, the interaction and dispersion state between the components are maintained, thus ensuring the uniformity of the final product. The appropriate cooling temperature can prevent the initial mixture from agglomerating and deteriorating during storage. Mixtures at high temperatures are prone to chemical reactions or physical changes during storage, resulting in performance degradation. After cooling to ≤55℃, the stability of the mixture is improved, which helps to extend its storage life.

[0030] Preferably, in the high-speed mixing step, the nucleating agent is stirred and mixed with other ingredients at a high speed to obtain a preliminary mixture.

[0031] In summary, this application has the following beneficial effects: Since the heat stabilizer used in the present application includes calcium zinc stabilizer and barium zinc stabilizer, the chemical reagent resistance of PVC can be improved, so that it can maintain stable performance in various chemical environments; the lubricant includes oxidized polyethylene wax and calcium stearate, which can improve the scratch resistance of PVC to a certain extent. In addition, the addition of acrylic processing aids can enhance the hardness and wear resistance of the PVC surface, thereby improving its scratch resistance; The present application also adds nucleating agents including tert-butyl aluminum benzoate, aluminum benzoate, potassium benzoate and lithium benzoate. The nucleating agent plays a role of heterogeneous nucleation in PVC, which can refine the grains of PVC and reduce the possibility of stress concentration and scratches caused by coarse grains; the addition of the nucleating agent can also improve the toughness of PVC and help reduce the generation and expansion of scratches. DETAILED DESCRIPTION

[0032] The raw materials in this application include the following parts: PVC resin: polyvinyl chloride resin, a commercially available product with CAS number 9002-86-2; Plasticizer: polyester plasticizer, epoxy soybean oil, etc. can be used. This application uses polyester plasticizer as an example and uses the commercially available product of Senya New Materials Co., Ltd.; Calcium zinc stabilizer: a commercially available product with the brand number 91660 produced by Baerlocher of Germany; Barium zinc stabilizer: a commercial product of Changhe Chemical New Materials Co., Ltd.; Acrylate processing aid: Use commercially available product of Japan's Kanebuchi brand chemical material PA20 model; Oxidized polyethylene wax: a commercially available product with CAS number 110119-84-1; Calcium stearate: a commercially available product with CAS number 1592-23-0; Phosphite: There are many types of phosphites, including triphenyl phosphite, triethyl phosphite, dimethyl phosphite, etc. This application uses dimethyl phosphite as an example, and uses a commercial product with a CAS number of 822-39-9; Aluminum tert-butylbenzoate: a commercially available product from Zhongkejian Chemical Co., Ltd. Aluminum benzoate: a commercially available product with CAS number 555-32-8; Potassium benzoate: a commercially available product with CAS number 582-25-2; Lithium benzoate: a commercially available product with CAS number 553-54-8; The present application is further described in detail below with reference to examples and comparative examples.

[0033] Example 1 A method for preparing a soft PVC composition comprises the following steps: High-speed mixing: 50kg PVC resin (average degree of polymerization is 700), 21kg polyester plasticizer, 3kg calcium zinc stabilizer, 1.5kg acrylic processing aid, 0.6kg oxidized polyethylene wax and 0.2kg phosphite are mixed at high speed, the stirring speed of high-speed mixing is 550rpm (500-600rpm is possible), the end temperature is 115℃ (that is, when the temperature reaches 115℃, high-speed mixing is stopped) to obtain an initial mixture; Cooling and mixing: the initial mixture is stirred and cooled and mixed for 1 hour at a low speed, the stirring speed of the low speed stirring is 30 rpm, and the cooling temperature of the cooling and mixing is 25° C. to obtain a final mixture; the cooling temperature in Example 1 is room temperature 25° C., and the cooling temperature can be further reduced to speed up the cooling speed; Extrusion granulation: The final mixture is extruded and granulated to obtain a soft PVC composition.

[0034] Embodiment 2-4 Example 2-3 Based on the preparation method of Example 1, the content of each component of the soft PVC composition is adjusted, and the specific adjustment is shown in Table 1.

[0035] Example 4 Based on the preparation method of Example 1, 0.6 kg of calcium stearate is replaced by 0.6 kg of oxidized polyethylene wax.

[0036] Comparative Example 1-2 Comparative Example 1-2 Based on the preparation method of Example 1, the content of each component of the soft PVC composition was adjusted, and the specific adjustment is shown in Table 1.

[0037] Table 1 Contents of components and performance test table of the soft PVC compositions of Examples 1-4 and Comparative Examples 1-2

[0038] Performance testing After the polypropylene was modified with the hexahydrophthalic acid of Examples 1-4 and Comparative Examples 1-2, the following performance tests were performed. The test results are shown in Table 1.

[0039] 1. Scratch resistance The scratch resistance of plastic parts was determined according to method A in GMW 14688, with a load of 10N and the cross scratch △L value was recorded.

[0040] 2. Weight loss rate The soft PVC composition was made into a 10cm*10cm*2cm thin sheet, and the sheet mass M0 was recorded. 0.2mL gasoline and 0.2mL diesel were mixed and dropped on the surface of the sheet, and placed at room temperature for 1 hour, and then placed in a 60℃ oven for 4 hours. After the sheet was taken out after the reaction, the residual solution was absorbed with absorbent paper, and the sheet mass M1 after the reaction was recorded. The weight loss rate was calculated as [(M0-M1) / M0]*100%.

[0041] Referring to Table 1, it can be seen from the comparison between Examples 1-4 and Comparative Examples 1-2 that the cross scratch ΔL value and weight loss rate of Examples 1-4 are much lower than those of Comparative Examples 1-2, indicating that the addition of calcium zinc stabilizer can effectively improve the scratch resistance of PVC, and the addition of oxidized polyethylene wax can effectively improve the chemical resistance of PVC.

[0042] In addition, by comparing Examples 1-4, it is found that Example 1 has the best comprehensive performance, so Example 1 is preferred.

[0043] Embodiment 5-10 Example 5 Based on the preparation method of Example 1, 3 kg of calcium zinc stabilizer is replaced with 3 kg of a mixture of calcium zinc stabilizer and barium zinc stabilizer, and the mass ratio of the calcium zinc stabilizer to the barium zinc stabilizer in the mixture is 1:2.

[0044] In Example 6-9, based on the preparation method of Example 1, the mass ratio of the calcium zinc stabilizer to the barium zinc stabilizer was adjusted. The specific adjustment is shown in Table 2.

[0045] Example 10 Based on the preparation method of Example 1, 3 kg of calcium zinc stabilizer is replaced with 3 kg of barium zinc stabilizer.

[0046] The soft PVC compositions of Examples 5-10 were subjected to the above performance tests, and the test results are shown in Table 2.

[0047] Table 2 Mass ratio of zinc stabilizer and barium zinc stabilizer and performance test table of Example 1 and Examples 5-10

[0048] Referring to Table 2, it can be seen from the comparison between Example 1 and Examples 5-10 that the soft PVC composition made from the mixture of calcium zinc stabilizer and barium zinc stabilizer is better than the soft PVC composition made from either of them alone. It is possible that the calcium zinc stabilizer and the barium zinc stabilizer have certain complementarity in performance. The calcium zinc stabilizer is good at processing performance and environmental protection, while the barium zinc stabilizer is good at improving hardness and strength. The mixed use of the two can give full play to their respective advantages, so that the PVC products show superior performance in many aspects.

[0049] As the mass ratio of calcium zinc stabilizer to barium zinc stabilizer gradually decreases, the cross scratch △L value and weight loss rate show a gradually decreasing trend, which may be because the barium zinc stabilizer can significantly improve the hardness and strength of PVC, thereby improving the scratch resistance and chemical resistance of the soft PVC composition. When the mass ratio of calcium zinc stabilizer to barium zinc stabilizer exceeds a certain range, the cross scratch △L value and weight loss rate show a gradually increasing trend, which may be because too high a content of barium zinc stabilizer may have an adverse effect on processing performance, such as increasing resistance during extrusion or injection molding, thereby reducing the scratch resistance and chemical resistance of the soft PVC composition.

[0050] Examples 11-14 In Examples 11-14, based on the preparation method of Example 1, the average degree of polymerization of the PVC resin was adjusted. The specific adjustments are shown in Table 3.

[0051] The soft PVC compositions of Examples 11-14 were subjected to the above performance tests, and the test results are shown in Table 3.

[0052] Table 3 Average degree of polymerization and performance test table of PVC resin of Example 1 and Examples 11-14

[0053] Referring to Table 3, it can be seen from the comparison between Example 1 and Examples 11-14 that, as the average degree of polymerization of the PVC resin continues to increase, the cross-scratch ΔL value and the weight loss rate show a gradually decreasing trend, which may be because the barium zinc stabilizer can significantly improve the hardness and strength of the PVC, thereby improving the scratch resistance and chemical resistance of the soft PVC composition. When the mass ratio of the calcium zinc stabilizer to the barium zinc stabilizer exceeds a certain range, the cross-scratch ΔL value and the weight loss rate show a gradually increasing trend, which may be because an excessively high content of the barium zinc stabilizer may have an adverse effect on the processing performance, such as increasing the resistance during extrusion or injection molding, thereby reducing the scratch resistance and chemical resistance of the soft PVC composition.

[0054] Examples 15-18 Example 15 is based on the preparation method of Example 1, and 0.3 kg of aluminum tert-butyl benzoate is added and mixed with other ingredients such as PVC resin at high speed, while other conditions remain unchanged.

[0055] In Examples 16-18, based on the preparation method of Example 15, the amount of aluminum tert-butylbenzoate added was adjusted. The specific adjustments are shown in Table 4.

[0056] The soft PVC compositions of Examples 15-18 were subjected to the above performance tests, and the test results are shown in Table 4 respectively.

[0057] Table 4 Addition amount and performance test table of tert-butyl benzoate aluminum in Example 1 and Examples 15-18

[0058] Referring to Table 4, by comparing Example 1 with Examples 15-18, it can be seen that the addition of aluminum tert-butylbenzoate plays a role of heterogeneous nucleation, which can refine the grains of PVC, thereby further improving the scratch resistance and chemical resistance of the soft PVC composition.

[0059] As the amount of aluminum tert-butylbenzoate added increases, the cross scratch △L value and weight loss rate show a gradually decreasing trend. This may be because after the grain refinement, the surface of the PVC product is more uniform and delicate, reducing the possibility of stress concentration and scratches caused by coarse grains. The addition of nucleating agents can also improve the toughness of PVC, making it more resistant to deformation when facing external forces. This improvement in toughness helps to reduce the generation and expansion of scratches, thereby further improving the scratch resistance of soft PVC compositions.

[0060] Examples 19-21 Examples 19-21 are based on the preparation method of Example 15, except that aluminum tert-butyl benzoate is replaced with other nucleating agents, and other conditions remain unchanged.

[0061] The soft PVC compositions of Examples 19-21 were subjected to the above performance tests, and the test results are shown in Table 5, respectively.

[0062] Table 5 Nucleating agent types and performance test table of Example 1, Example 15 and Examples 19-21

[0063] Referring to Table 5, it can be seen from the comparison of Example 1, Example 15 and Examples 19-21 that the addition of aluminum benzoate, potassium benzoate and lithium benzoate can also effectively improve the scratch resistance and chemical resistance of the soft PVC composition. Among them, aluminum tert-butyl benzoate and aluminum benzoate have certain polarity, and PVC is a polar polymer material. According to the principle of similar polarity, polar components have good compatibility with polar components. Therefore, these two nucleating agents have good compatibility with PVC, can be evenly dispersed in PVC, and exert better nucleating effect.

[0064] Examples 22-27 In Examples 22-27, based on the preparation method of Example 1, the termination temperature of high-speed mixing and the cooling temperature of cooling mixing are adjusted. The specific adjustments are shown in Table 6.

[0065] The soft PVC compositions of Examples 22-27 were subjected to the above performance tests, and the test results are shown in Table 6 respectively.

[0066] Table 6 Termination temperature, cooling temperature and performance test table of Example 1 and Examples 22-27

[0067] Referring to Table 6, it can be seen from the comparison between Example 1 and Examples 22-27 that as the termination temperature increases, the cross-scratch ΔL value and the weight loss rate show a decreasing trend, which may make it easier for many added components to be evenly mixed with the PVC resin in a molten state to form a stable initial mixture, thereby improving the scratch resistance and chemical resistance of the soft PVC composition. When the termination temperature exceeds a certain range, the cross-scratch ΔL value and the weight loss rate show a gradually increasing trend, which may be due to the overheating decomposition of the PVC resin, thereby reducing the scratch resistance and chemical resistance of the soft PVC composition.

[0068] As the cooling temperature continues to increase, the cross scratch △ L value and weight loss rate show a downward trend. It is possible that during the cooling process, the interaction and dispersion state between the components are maintained, thereby ensuring the uniformity of the final product, thereby improving the scratch resistance and chemical resistance of the soft PVC composition.

[0069] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.

Claims

1. A soft PVC composition, characterized in that: The invention comprises the following components in parts by weight: 50 parts of PVC resin, 15-40 parts of plasticizer, 2.5-4.5 parts of heat stabilizer, 1-2 parts of acrylic processing aid, 0.3-0.9 parts of lubricant, and 0.1-0.3 parts of phosphite; The heat stabilizer includes at least one of a calcium zinc stabilizer and a barium zinc stabilizer; The lubricant includes at least one of oxidized polyethylene wax and calcium stearate.

2. The soft PVC composition according to claim 1, characterized in that: The heat stabilizer is a mixture of a calcium zinc stabilizer and a barium zinc stabilizer.

3. The soft PVC composition according to claim 2, characterized in that: The mass ratio between the calcium zinc stabilizer and the barium zinc stabilizer is 1:1-2.

5.

4. The soft PVC composition according to claim 1, characterized in that: The average polymerization degree of the PVC resin is 600-800.

5. The soft PVC composition according to claim 1, characterized in that: The invention also includes a nucleating agent, which includes at least one of tert-butyl aluminum benzoate, aluminum benzoate, potassium benzoate and lithium benzoate.

6. The soft PVC composition according to claim 5, characterized in that: The nucleating agent is at least one of aluminum tert-butyl benzoate and aluminum benzoate.

7. The soft PVC composition according to claim 5, characterized in that: The weight portion of the nucleating agent is 0.1-0.3 parts.

8. The method for preparing the soft PVC composition according to any one of claims 1 to 4, characterized in that: The following steps are involved: High-speed mixing: mixing the formulated amount of PVC resin, plasticizer, heat stabilizer, acrylic processing aid, lubricant and phosphite with high-speed stirring to obtain a preliminary mixture, wherein the stirring speed of the high-speed stirring is 500-600 rpm; Cooling and mixing: the initial mixture is further subjected to low-speed stirring and cooling and mixing to obtain a final mixture, wherein the stirring speed of the low-speed stirring is 20-40 rpm; Extrusion granulation: The final mixture is subjected to extrusion granulation to obtain a soft PVC composition.

9. The method for preparing the soft PVC composition according to claim 8, characterized in that: In the high-speed mixing step, the termination temperature of the high-speed mixing is 100-125°C; in the cooling mixing step, the cooling temperature of the cooling mixing is ≤55°C.

10. The method for preparing the soft PVC composition according to claim 8, characterized in that: In the high-speed mixing step, the nucleating agent is mixed with other ingredients by high-speed stirring to obtain a preliminary mixture.

Citation Information

Patent Citations

  • Delustring medical soft PVC modified material with low temperature resistance and low DOP precipitation

    CN102020815A

  • Calcium / zinc thermal stabilizer polyvinyl chloride transparent hard film and preparation method thereof

    CN102174235A

  • Hard PVC (polyvinyl chloride) profile particle material with high brightness and high blackness on surface and manufacturing method of hard PVC profile particle material

    CN107586420A

  • Frosted PVC material for internal and external decoration strips of automobile and manufacturing method

    CN109627636A

  • Rigid medical injection molding PVC plastic with ultra-high transparency and high thermal stability

    CN110982198A